2004
DOI: 10.1111/j.1365-2125.2004.02224.x
|View full text |Cite
|
Sign up to set email alerts
|

A semimechanistic and mechanistic population PK–PD model for biomarker response to ibandronate, a new bisphosphonate for the treatment of osteoporosis

Abstract: AimsIbandronate, a highly potent nitrogen-containing bisphosphonate, is the subject of an ongoing clinical development programme that aims to maximize the potential of simplified, less frequent oral and intravenous (i.v.) administration in osteoporosis. A modelling and simulation project was undertaken to characterize further the clinical pharmacology of ibandronate and identify convenient intermittent oral and i.v. regimens for clinical evaluation. Methods and resultsUsing selected data from clinical studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 37 publications
2
77
0
3
Order By: Relevance
“…Post and Danhof presented a variety of equations for describing disease progression using pharmacodynamic indirect response models, a mechanistic paradigm for describing turnover of response and drug effect (Dayneka et al, 1993;Post et al, 2005). Other diseases have been described, including bacterial cell growth and irreversible loss after drug therapy, fasting plasma glucose in diabetes, and pain and bone mineral density progression in osteoarthritis (Jusko, 1971;Ravn et al, 1996;Meunier et al, 1999;Frey et al, 2003;Pillai et al, 2004;de Winter et al, 2006). Mechanism-based disease progression models are continually being derived because their insight into how various pathologies contribute to progression and how drugs exert their effects on specific processes is essential to optimizing therapy (Holford and Peace, 1992a,b;Nemeroff, 1994;Hoogendoorn et al, 2005;Holford et al, 2006;Meier et al, 2007;Woo et al, 2008).…”
mentioning
confidence: 99%
“…Post and Danhof presented a variety of equations for describing disease progression using pharmacodynamic indirect response models, a mechanistic paradigm for describing turnover of response and drug effect (Dayneka et al, 1993;Post et al, 2005). Other diseases have been described, including bacterial cell growth and irreversible loss after drug therapy, fasting plasma glucose in diabetes, and pain and bone mineral density progression in osteoarthritis (Jusko, 1971;Ravn et al, 1996;Meunier et al, 1999;Frey et al, 2003;Pillai et al, 2004;de Winter et al, 2006). Mechanism-based disease progression models are continually being derived because their insight into how various pathologies contribute to progression and how drugs exert their effects on specific processes is essential to optimizing therapy (Holford and Peace, 1992a,b;Nemeroff, 1994;Hoogendoorn et al, 2005;Holford et al, 2006;Meier et al, 2007;Woo et al, 2008).…”
mentioning
confidence: 99%
“…Application of the K‐PD approach in clinical trials has been reported to sufficiently describe the time course of PD data in the absence of drug concentration measurements 12, 13, 14, 15. A bone biomarker analysis in urine (bone resorption marker urine C‐terminal telopeptide in osteoporosis treatment with bisphosphonate) used a similar approach to our biomarker analysis, with a K‐PD model 16. They evaluated drug regimens in ongoing clinical development with both K‐PD and pharmacokinetic (PK)‐PD models and concluded that the K‐PD model adequately described the biomarker response.…”
Section: Study Highlightsmentioning
confidence: 99%
“…Since the work of Smolen, DRT data analysis has been proven to be applicable to novel sys- 20 tems where the kinetics and/or dynamics behave non-linearly, when there are time-delays in the response data, and when the system contains feedback mechanisms [24]. The technique has successfully been applied in models of the muscle relaxant drug vecuronium [14,22,21,64], antinociceptive drugs [1,26,24], ophthalmic drugs [24,41], antidepressants [28], psycho-motor stimulants [26], drugs 25 to treat chronic obstructive pulmonary disease (COPD) [65], and osteoporosis [46]. For a review and theoretical guide to DRT analysis see Gabrielsson et al.…”
Section: Introductionmentioning
confidence: 99%
“…[24,26]. DRT models go under the name of K-PD (K for kinetic) models in some analyses [28,29,35,46,65]. However, in the latter case the biophase turnover rate, rather than the biophase amount, is driving the response.…”
Section: Introductionmentioning
confidence: 99%